Function, mechanism and drug discovery of ubiquitin and ubiquitin-like modification with multiomics profiling for cancer therapy - Yanyu Jiang; Shuaishuai Ni; Biying Xiao; Lijun Jia (Acta Pharmaceutica Sinica B, 2023)
Ubiquitin (Ub) and ubiquitin-like (Ubl) pathways are critical post-translational modifications that determine whether functional proteins are degraded or activated/inactivated. To date, >600 associated enzymes have been reported that comprise a hierarchical task network (e.g., E1–E2–E3 cascade enzymatic reaction and deubiquitination) to modulate substrates, including enormous oncoproteins and tumor-suppressive proteins. Several strategies, such as classical biochemical approaches, multiomics, and clinical sample analysis, were combined to elucidate the functional relations between these enzymes and tumors. In this regard, the fundamental advances and follow-on drug discoveries have been crucial in providing vital information concerning contemporary translational efforts to tailor individualized treatment by targeting Ub and Ubl pathways. Correspondingly, emphasizing the current progress of Ub-related pathways as therapeutic targets in cancer is deemed essential. In the present review, we summarize and discuss the functions, clinical significance, and regulatory mechanisms of Ub and Ubl pathways in tumorigenesis as well as the current progress of small-molecular drug discovery. In particular, multiomics analyses were integrated to delineate the complexity of Ub and Ubl modifications for cancer therapy. The present review will provide a focused and up-to-date overview for the researchers to pursue further studies regarding the Ub and Ubl pathways targeted anticancer strategies.